Solvent extraction of butanol from synthetic solution and fermentation broth: batch and continuous studies - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Gaikwad, Shashank G.; Chavan, V, Prakash; Bankar, Sandip B. (Separation and Purification Technology, 2020)
Product recovery is one of the essential finishing steps to any commercial fermentation process. In acetone-butanol-ethanol (ABE) fermentation, butanol recovery is quite tedious mainly due to dilute product and multiple byproduct formation in complex media. Among different recovery methods, extraction has attracted considerable attention in biofuel recovery owing to its high selectivity, low energy consumption, and ease of operation. In present work, the butanol extraction performance from synthetic solvent mixture containing ABE was tested in batch and continuous operations using 20% (v/v) decanol in oleyl alcohol. The optimized extraction conditions were then validated using actual fermentation broth to confirm effectiveness of the extraction operation. The distribution coefficient (K-d) and batch extraction efficiency (E) were in the range of 5.60-9.80 and 87.70-86.90% for fermentation broth and synthetic solution, respectively for a given initial concentration of butanol in the aqueous phase. Further, E was relatively improved by supplementing different inorganic salts. Sodium hydroxide (5%, w/v) was highly effective to recover butanol from fermentation broth (E similar to 97.70%) with K-d of 33.10. Besides, the continuous counter current extraction of butanol in a packed column was performed. The volumetric mass transfer coefficient (kLa) was estimated to be 0.025 1/min at an optimized superficial velocity of the aqueous phase (0.28 cm/min) and sodium hydroxide concentration (5%, w/v). Height of the extraction column was estimated to be 28.32 cm using height of transfer unit (HTU) and number of transfer unit (NTU) concept for extraction efficiency of 97.20%. Overall, the present study has demonstrated an enhanced extraction efficiency of butanol from fermentation broth.
Keywords: Biobutanol; Equilibrium stages; Height of transfer unit; liquid-liquid extraction; mass transfer coefficient; Number of transfer unit